Primary healthcare services' accessibility and quality under compulsory social health insurance in Kazakhstan - Makhabbat Shurenova; Kuralbay Kurakbayev; Tleukhan Abildaev; Aigul Tazhiyeva (Frontiers Media S.A., 2024)
IntroductionBetween 2020 and 2022, there was a rise in employment and entrepreneurial activity, despite some unemployment growth. In the Compulsory Social Health Insurance (CSHI), insured individuals, especially privileged and wage workers, increased. However, certain contributors, like those exempt from contributions and single social taxpayers, decreased, possibly due to legislative changes or the economic climate. The study aimed to evaluate the effectiveness and accessibility of medical services within the frameworks of Compulsory Social Health Insurance and the state Guaranteed volume of free medical care based on data regarding waiting times and the volume of services provided.MethodsThis retrospective study analyzed data from 2020 to 2022 on patients receiving care under Kazakhstan's Mandatory Social Medical Insurance System (MSMIS) and Guaranteed Volume of Free Medical Care. Data included insurance status, labor market indicators, and medical service procurement. Descriptive statistics were calculated, and t-tests, with p-values indicating statistical significance (p < 0.05).ResultsIt has been identified that overall, the execution of the plan for all types of medical care in Kazakhstan, including Almaty, reaches 100.0%, indicating sufficient financial support for the healthcare system. Rehabilitation centers and COVID-19 testing services stand out with shorter waiting times, whereas comprehensive diagnostic and advisory services require significantly longer waiting periods. The Guaranteed Volume of Free Medical Care typically offers a greater number of services with shorter waiting times compared to MSMIS, except for specialized medical care services in diagnosing new formations, where the Guaranteed Volume of Free Medical Care also has shorter waiting times but provides a greater number of services.ConclusionThe study has allowed us to identify differences in the availability and volume of medical services provided between Compulsory Social Health Insurance and the state Guaranteed volume of free medical care.